Vitamin D-VDR (vitamin D receptor) alleviates glucose metabolism reprogramming in lipopolysaccharide-induced acute kidney injury - Dai, Qing; Zhang, Hao; Tang, Shiqi; Wu, Xueqin; Wang, Jianwen; Yi, Bin; Liu, Jishi; Li, Zhi; Liao, Qin; Li, Aimei; Liu, Yan; Zhang, Wei (Frontiers in Physiology, 2023)
Our previous study showed that vitamin D (VD)-vitamin D receptor (VDR) plays a nephroprotective role in lipopolysaccharide (LPS)-induced acute kidney injury (AKI). Recently, glucose metabolism reprogramming was reported to be involved in the pathogenesis of AKI. To investigate the role of VD-VDR in glucose metabolism reprogramming in LPS-induced AKI, we established a model of LPS-induced AKI in VDR knockout (VDR-KO) mice, renal proximal tubular-specific VDR-overexpressing (VDR-OE) mice and wild-type C57BL/6 mice. We observed that paricalcitol (an active vitamin D analog) or VDR-OE reduced lactate concentration, hexokinase activity and PDHA1 phosphorylation (a key step in inhibiting aerobic oxidation) and simultaneously ameliorated renal inflammation, apoptosis and kidney injury in LPS-induced AKI mice, which were more severe in VDR-KO mice. In in vitro experiments, glucose metabolism reprogramming, inflammation and apoptosis induced by LPS were alleviated by treatment with paricalcitol or dichloroacetate (DCA, an inhibitor of p-PDHA1). Moreover, paricalcitol activated the phosphorylation of AMP activated protein kinase (AMPK), and an AMPK inhibitor partially abolished the protective effect of paricalcitol in LPS treated HK-2 cells. In conclusion, VD-VDR alleviated LPS-induced metabolic reprogramming in the kidneys of AKI mice, which may be attributed to the inactivation of PDHA1 phosphorylation via the AMPK pathway.